Biodiversity The Dynamic Balance of the Planet - Grillo, Oscar (IntechOpen, 2014)
The current world biodiversity consists of an inestimable amount of living forms, that at all levels, from genes to biomes, from individuals to populations, from species to communities, are in constant pursuit of the best strategies to react to the natural and anthropic environmental changes. The arrangement of new and dynamic ecosystems balanced by the formation and the vanishing of species, is the direct consequence of these changes. This book contains comprehensive overviews and original studies focused on ecological and ecosystem functioning studies, hazards and conservation management, assessment of environmental variables affecting species diversity, also considering species richness and distribution, in order to identify the best management strategies to face and solve the conservation problems.